2023
DOI: 10.3390/ijms24055019
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Association Study and Transcriptome of Japanese Patients with Developmental Dysplasia of the Hip Demonstrates an Association with the Ferroptosis Signaling Pathway

Abstract: This study examined the association between developmental dysplasia of the hip (DDH) and disease-associated loci in a Japanese cohort. A genome-wide association study (GWAS) of 238 Japanese patients with DDH and 2044 healthy individuals was performed. As a replicate, GWAS was also conducted on the UK Biobank data with 3315 cases and matched 74,038 controls. Gene set enrichment analyses (GSEAs) of both the genetics and transcriptome of DDH were performed. Transcriptome analysis of cartilage specimens from DDH-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 60 publications
0
1
0
Order By: Relevance
“…Genome-wide screening has revealed that familial hip OA is associated with acetabular dysplasia 36 , and a recent genome-wide association study and transcriptome analysis found an association between the ferroptosis signaling pathway and DDH 37 . In an epidemiological study using data from the Rochester Epidemiology Project, LaPrade et al found that only 156 (8%) of 1,893 patients <50 years of age with hip pain had hip dysplasia 38 .…”
mentioning
confidence: 99%
“…Genome-wide screening has revealed that familial hip OA is associated with acetabular dysplasia 36 , and a recent genome-wide association study and transcriptome analysis found an association between the ferroptosis signaling pathway and DDH 37 . In an epidemiological study using data from the Rochester Epidemiology Project, LaPrade et al found that only 156 (8%) of 1,893 patients <50 years of age with hip pain had hip dysplasia 38 .…”
mentioning
confidence: 99%